2020
DOI: 10.1371/journal.pone.0228496
|View full text |Cite
|
Sign up to set email alerts
|

The distal intestinal microbiome of hybrids of Hainan black goats and Saanen goats

Abstract: Intestinal microbiota performed numerous important functions during digestion. The first filial generation (F1) hybrids of Hainan black goats and Saanen goats had different traits, black goats (BG) and white goats (WG), which also brought different production performance. We explored the difference of gut microbiota between black goats and white goats that both belonged to the first filial generation (F1) hybrids. In general, the alpha diversity of the black goat group was significantly higher than the white g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A similar study in sheep indicated that the abundance of microbial ABC transporters differed between Tibetan and Small Tail Han breeds grown under the same environmental conditions [ 41 ]. In addition, the metabolic pathways of carbohydrates (fructose, mannose, and galactose), amino acids (BCAAs, AAAs, and lysine), and lipids (glycerolipid) have been shown to differ among farm animal breeds grown under the standardized feeding conditions [ 6 , 42 45 ]. The breed-associated KEGG pathways showed substantial overlap with the breed-associated KOs.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in sheep indicated that the abundance of microbial ABC transporters differed between Tibetan and Small Tail Han breeds grown under the same environmental conditions [ 41 ]. In addition, the metabolic pathways of carbohydrates (fructose, mannose, and galactose), amino acids (BCAAs, AAAs, and lysine), and lipids (glycerolipid) have been shown to differ among farm animal breeds grown under the standardized feeding conditions [ 6 , 42 45 ]. The breed-associated KEGG pathways showed substantial overlap with the breed-associated KOs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown dysbiosis of the human gut microbiota in obese individuals ( 4 ). In many previous studies, when germ-free (GF) mice were inoculated with feces or the microbiota of obese human subjects, they developed symptoms such as increased weight and many obesity-associated metabolic phenotypes ( 5 , 6 ). Dietary elements have the ability to alter the community structure of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Hainan Island, in the South China Sea, has a tropical climate that is hot and humid, prompting the local animals to have differences from intensive commercial species in physical and life modes ( Zhu, 2016 ). Hainan black goats and Wuzhishan pigs are native breeds that have long been bred in the unique natural ecological environment of Hainan Island ( Jiang et al, 2020 ; Shao et al, 2021 ). In addition, the Wuzhishan pig is a famous miniature pig breed and is regarded as an ideal experimental animal model ( Shao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%